A modified approach for eminectomy for temporomandibular joint dislocation under local anaesthesia: report on a series of 50 patients. Issue 11 (November 2018) - Segami, N.
Abstract: Conventional eminectomy for habitual dislocation of the temporomandibular joint is usually performed under general anaesthesia. This technique was modified for use under local anaesthesia to treat medically compromised patients. Fifty elderly patients (90 joints) were treated, for whom general anaesthesia was considered a serious risk due to systemic diseases; the dislocation was habitual in 39 and long-standing in 11. Following intravenous sedation and local anaesthesia, a 2-cm superficial vertical skin incision was made directly above the articular eminence. Careful and gentle dissection of the subcutaneous tissue was performed until the lateral joint capsule was exposed. The superior compartment was entered, followed by shaving of the articular eminence in a conventional manner. The surgery was successful in all patients, with a mean operative time of 47 ± 12 minutes. Intraoperative events occurred in 10 patients (20%). Postoperative complications affected 25 patients (50%), varying from severe (two deaths, due to cardiopulmonary arrest and accidental fall) to mild (local infection, etc.). Eleven patients (22%) had facial nerve palsy limited to the temporal branch; all recovered after 6 months. This approach is useful when general anaesthesia is contraindicated due to existing medical conditions. However, prudent consideration may be required to avoid serious complications when local anaesthesia is used.